Fostering food and energy security through by-product valorization within agricultural and agro-industrial networks: study of the province of Santiago de Cuba. Issue 2 (4th March 2017) - Concha, Daniela; Adams, Michelle; Suárez, José; Faxas, Ronoldy
ABSTRACT: The aim of this study is to investigate of how the concept of 'integrated food and energy systems' or IFES production networks could be applied – within the specific context of Eastern Cuba's agricultural and agro-industrial sectors – as an innovative approach to improve food and energy security. The Province of Santiago de Cuba in southeast Cuba was the focus of this study; its existing operations, infrastructure, resource flows and scarcities, and actor relationships provide the basis of the data used for the evaluation. The authors investigated the regional context, identify potential members of an agricultural and agro-industrial network in three municipalities of the province, and identify the main residuals and by-products of key facilities. Potential avenues for by-product valorization are investigated along with the possible influence/impacts on the sustainability of the surrounding systems and actors. A conceptual model for a regional network for integrated food and energy production is then provided based upon the development of three agricultural/agro-industrial scenarios: influence at the farm level, regional agro-industrial networks, and 'anchor tenant' eco-industrial systems. The main challenges and opportunities for the development of the networks are described with recommendations for addressing such where possible.